(untitled) (MAUSAM, 1966)
Recorded times of p and S phases as observed in different observatories in India during the TING period 1955, 1956 and 1957 on account of earthquakes having epicentres in and near the Indian subcontinent were collected from the Seismological Bulletins of the India Meteorological Department. The distances of the epicentres were determined and travel time curves for p and S waves were prepared. The observed velocities are fairly in good agreement with those determined by other workers for this region.